How Does Social Media Contribute to Improve Business Performance for Streaming Service? - Lay Hong Tan; Anurag Hazarika; Nur Farah Alyaa Ahmad Tamizi; Nur Arniesya Ahmad Nazri; Nur Athirah Mat Fuzi; Pranjal Saxena; Nur Farhana Mohd Affandi (AIBPM Publisher, 2024)
In a rapidly evolving technological landscape, organizations are constantly seeking innovative strategies to enhance performance and connect with their target audience. One such platform gaining traction is TikTok, a social media network particularly popular among young people. Recognizing its potential, businesses are exploring how TikTok can foster brand awareness and cultivate deeper consumer engagement. This study investigates whether factors like internet consumption patterns, social influence on TikTok, perceived value of TikTok content for Netflix, and trust in Netflix as a brand contribute to its performance. Interestingly, through a survey administered to 151 participants, the research suggests that internet consumption is the primary driver, with social influence, perceived usefulness, and trust on TikTok not having a statistically significant impact on Netflix's performance. This study suggests that for Netflix, user engagement with its content is the crucial factor on TikTok, not relying on influencer marketing or specific content value perceptions. Future research should explore content formats, user interaction strategies, and audience segmentation techniques to maximize user engagement with Netflix content on the platform.